Optimalisasi masyarakat melalui Pendidikan Life Skill berbasis Teknologi Desa Tanjung Setia - Subandi, Subandi; Irawan, Bambang; sya’adi, Nur; Apriyadi, Muchsin (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the effectiveness of technology-based life skill education in empowering the community of Tanjung Setia Village, Krui, Pesisir Barat. The village has significant economic potential as a marine tourism destination; however, most residents still rely on traditional livelihoods with limited digital skills and business management capabilities. The community service program employed the Asset-Based Community Development (ABCD) framework to identify, develop, and utilize local assets while enhancing life skills and technological capabilities. Methods used included observation, interviews, Focus Group Discussions (FGDs), training, and continuous mentoring. The results indicated significant improvements in practical skills, digital media usage, online marketing strategies, business productivity, and economic independence of the community. Active participation in digital communities also strengthened collaborative networks and ensured program sustainability. These findings confirm that technology-based life skill education is a strategic instrument for enhancing community welfare and maximizing local economic potential.